Width of cleft palate and postoperative palatal fistula - Do they really correlate? - Rakesh Kumar Khazanchi; Hardeep Singh (Wolters Kluwer Medknow Publications, 2020)
Background: Palatal Fistula according to previous studies is directly proportional to width of the clefts. The fallacies with these studies were presence of multiple confounding factors such as multiple surgeons using different techniques of repair. Aim: This study attempted to assess the correlation between the actual width of cleft (W) and ratio of cleft width to sum of width of palatal shelves (R) with the incidence of palatal fistula done by single surgeon using same standardized repair thus eliminating bias due to multiple variables. Methods: This study includes consecutive cases of palatoplasty over 18 months. Bardachs 2 flap palatoplasty with radical Muscle dissection was performed. Palatal fistula was assessed at 3 weeks and at 2months. Results were analyzed with Wilcoxon signed rank test. Results: The values of W and R were analyzed in 45 patients. At 3 weeks 4 patients had fistula (8.9%) while at 2 months follow up only one patient (2.2%) had it. In patients without a fistula (n=41), the mean W was 1.22+0.31 cms SD (range 0.4 to 1.9cm) and R was 0.47+0.14 SD (range 0.15 to 0.83). In 4 patients with fistula at 3 weeks, the mean W was 1.28+0.39 cm SD (range 0.90 tp 1.8 cm) and R was 0.60+0.37 SD (range 0.35 to 1.13). This difference was not statistically significant (P value- 1.000 and 0.968 respectively). Conclusion: This study shows correlation between the width of the cleft or the width of palatal shelves have no significant influence on palatal fistula. The high incidence in previous studies may be related to surgical techniques.